Surfactant-free synthesis protocol of robust and sustainable molten salt microcapsules for solar thermal energy storage - Lee, Jaejun; Jo, Byeongnam (Solar Energy Materials and Solar Cells, 2021)
This study synthesized robust and sustainable microcapsules of NaNO3 salt for harnessing solar thermal energy. The NaNO3 salt was encapsulated into SiO2 shells without the use of surfactants using a sol-gel process. The effects of the concentrations of precursor and catalyst, along with the synthesis time duration, were investigated to determine the optimal synthesis protocol for the solid NaNO3@SiO2 microcapsules. The morphological characteristics, including the shell structures of the NaNO3@SiO2 microcapsules, were examined using scanning electron microscopy. In addition, the elemental analysis was performed using Energy-dispersive X-ray spectroscopy and Fourier transform infrared spectrometry to prove the existence of the core and shell materials in the synthesized microcapsules. In addition, based on the thermal properties of the synthesized microcapsules as measured experimentally using differential scanning calorimetry (DSC), the encapsulation ratio and encapsulation efficiency were evaluated quantitatively. A high encapsulation ratio (85.8%) and a high encapsulation efficiency (87.4%) were achieved under the optimal synthesis protocol suggested in this study. The heat storage capacity of the microcapsules was estimated as the temperature increased from 250 to 350 °C and compared to that of the solar salts. The outstanding thermal reliability and stability of the NaNO3@SiO2 microcapsules were determined based on repeated heating and cooling cycles in the DSC measurements. Additionally, their long-lasting heating capabilities (up to 12 h at 350 °C) were confirmed, providing options for their use in solar thermal energy storage applications.
Keywords: Encapsulation efficiency; Energy dispersive X ray spectroscopy; Fourier transform infrared spectrometry; Heat storage capacity; Heating and cooling cycles; Morphological characteristic; Solar thermal energy; Thermal reliability; Concentrating solar power; Molten salt; Surfactant-free microencapsulation; Thermal energy storage; Thermal reliability